SIMULASI DAN ANALISIS DAMPAK PLTS DAN BESS TERHADAP DROP TEGANGAN PADA SISTEM KELISTRIKAN NUSA PENIDA - Pranipata, IND; Kumara, INS; Sukerayasa, IW; Giriantari, IAD; Setiawan, IN; Ariastina, WG (Jurnal SPEKTRUM; Vol 11 No 2 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i02.p23, 2024)
Nusa Penida, Nusa Ceningan, and Nusa Lembongan or known as Tiga Nusa are very famous tourist destinations in Bali Province. The growth of tourism in Tiga Nusa has resulted in demand for electrical energy increasing every year. In order to meet the electrical energy needs in Tiga Nusa, the PLN continues to strive to improve the quality of the Nusa Penida electricity system. One of PLN's efforts is to build a Solar Power Plant that is interconnected with BESS. This research aims to analyze the effect of Solar Power Plant and BESS on voltage drops in the Nusa Penida electricity system. This research was carried out by simulation using electricity system dynamic simulation software. The simulation will be carried out with 3 scenarios. The results of this research are that Solar Power Plant interconnected with BESS has a good influence on the Nusa Penida Electricity System, as evidenced by the simulation results for scenarios 2 and 3 which have better voltage drop values compared to scenario 1.